A review of the leafhopper genus Pseudosubhimalus Ghauri (Hemiptera: Cicadellidae: Deltocephalinae) with description of a new species from Pakistan - Naveed, Hassan; Shah, Bismillah; Zhang, Yalin (Zootaxa, 2020)
A new species of the leafhopper genus Pseudosubhimalus Ghauri (Cicadellidae: Deltocephalinae: Cicadulini), Pseudosubhimalus pakistanicus sp. n., is described from Khyber Pakhtunkhwa Province, Pakistan. Figures for habitus and genitalic characters are given for this new species and newly recorded species from Pakistan. A key to all the known species of the genus Pseudosubhimalus is provided.